Development of Spatial Models in Making Decisions on Suitable Area for Smart Farming at Agriculture Polytechnic of Samarinda - F. V. Astrolabe Sian Prasetya; Nia Kurniadin; M. Faisal Abimanyu (Politeknik Pertanian Negeri Samarinda, 2023)
In the context of fulfilling food, especially for agricultural and plantation commodities in East Kalimantan and fulfilling the Agriculture Polytechnic of Samarinda research strategic plan on Strengthening the Application of GIS and Remote Sensing for Land Management in the Agro-Ecosystem Zone, it is necessary to conduct studies related to determining suitable locations for smart farming in the location of the Agriculture Polytechnic of Samarinda. The closest technique in this study is to make a land model that is suitable for smart farming. The model was created by utilizing spatial data derived from remote sensing data, and also analyzed using GIS techniques. Several agricultural and plantation commodities have criteria as conditions for growth that must be met for each commodity. These parameters are conditions of humidity, temperature, and intensity of sunlight, where these data can be extracted from remote sensing data. By utilizing the NDVI, NDMI, and LST algorithms, as well as shadow analysis at the time of irradiation, it will be possible to model an area suitable for smart farming. By using spatial data from sentinel 2 and applying the NDMI, NDVI, and LST algorithms, it can be determined specifically which areas are suitable for several agricultural and plantation commodities. From the results of this study, it was found that several commodities could grow optimally in almost every location at the Agriculture Polytechnic of Samarinda, such as for the commodities of strawberry, rubber crop and robusta coffee. As for the commodities of Mustard Greens, Pepper, Cocoa, and Arabica Coffee, they are not suitable for planting in the Agriculture Polytechnic of Samarinda.